Biochemical Effect of Two Molluscicide Baits against the Land Snail Theba Pisana (Global Journal of Science Frontier Research, 2014)
An eight week feeding trial was conducted to evaluate the potential of Gliricidia maculata leaf meal as dietary protein source in the diet of Cirrhinus mrigala fingerlings. Four experimental diets were formulated to contain 20%, 30%, 40% and 50% G. maculata leaf meal (Diets 1 -4) to partially replace other protein ingredients in the C. mrigala diet. The diet containing 0% leaf meal served as the control. Each dietary treatment was tested in triplicate groups of 10 fingerlings. The results of the growth and feed utilization responses show that there were no significant differences among the fish fed diets 1 -3 but were significantly different from fish fed on diet 4 which had lower growth and feed utilization values. The present findings show that G. maculata leaf meal has good potential for use as one of the protein sources in C. mrigala diet up to 40% level without compromising growth.
Keywords: theba pisana; methomyl; diazinon; aspartate amino transaminase (ast); alanine amino transaminase (alt) and alkaline phosphatase (alk)